Evaluation of genetic divergence in radish (Raphanus Sativus L.) Germplasm using multivariate approaches in north-western Himalayas (Bangladesh Journal of Botany, 2025)
The present study was conducted to evaluate genetic divergence among 18 radish (Raphanus sativus L.) genotypes. High heritability was recorded for ascorbic acid, days to 50% germination, and root diameter. Correlation analysis revealed a positive association between root yield and traits such as root weight, root length, and plant height, while path analysis identified root weight, root diameter, and leaf traits as key yield contributors. Principal Component Analysis (PCA) revealed that the first two principal components explained a major portion of total variability, with PC1 strongly associated with yield traits and the first five principal components (PCs) explain 80.9% of the total variance, and PC1 contributing the most (31.3%). Hierarchical clustering grouped genotypes into distinct clusters, indicating diverse genetic backgrounds and potential for targeted breeding. These findings provide valuable insights for selecting superior genotypes to enhance radish breeding and production across diverse agro-climatic conditions.Bangladesh J. Bot. 54(3): 491-497, 2025 (September)